Prospect of Islamic Electronic Money in Indonesia: Case Study on the LinkAja Application - Hasan, Zulfikar; Jayanti, Endah Dwi; Azlina, Nur; Lestari, Reski; Muslim, Muslim (JESI (Jurnal Ekonomi Syariah Indonesia), 2022)
This research conducted to see how the prospects for electronic money in Indonesia, considering the launch of new electronic money launched this year through the LinkAja application. This application has received a fatwa from the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) to be a strong source of law for application in Indonesian society. The emergence of LinkAja electronic money is one of the policies of all stakeholders because the potential of sharia-based electronic money is quite large, apart from Indonesia having the world's largest Muslim population. The method that the author made is a qualitative method besides reading several journals and reading material about Islamic electronic money. The prospect of newly launched electronic money certainly has several challenges and opportunities that can be used as lessons for relevant stakeholders. Apart from the competition with the same applications as conventional-based electronic money, Indonesians are still used to conventional-based electronic money there is when compared to sharia-based systems. Complete support from the government is needed to make this electronic money develop well, apart from being protected by applicable laws and regulations. Promotion and marketing of all LinkAja management are also necessary to expand the reach not only in cities but also in villages.